TRANSFORMASI BUDAYA MUTU SEKOLAH DASAR DI ERA MERDEKA BELAJAR DI SDN JATIBARANG 01 SEMARANG - Listiyorini; Susi Agustin, Trifena; Haryati, Titik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The transformation of quality culture in primary schools has become a strategic necessity in the era of Merdeka Belajar (Freedom to Learn), where educational institutions are expected to function as centers of reflective, autonomous, and data-driven learning. This study aims to describe the process of transforming the quality culture at SDN Jatibarang 01 Semarang through the integration of data from the Rapor Pendidikan (Education Report) into the PPEPP-based quality management cycle (Planning, Implementation, Evaluation, Control, and Improvement). A qualitative approach was employed, utilizing participatory observation, interviews, and document analysis. The findings indicate that the school has fostered a collaborative and participatory culture of quality through the strengthening of professional learning communities, transformational leadership, and the effective use of the Rapor Pendidikan as a basis for decision-making. The main challenges identified include inconsistencies in program implementation and limited parental involvement. These findings contribute to the discourse on data-driven quality management practices in primary education and enrich the literature on institutional culture transformation in schools.